Push and Pull Motivations of Entrepreneurs with Disabilities in Hungary - Zsuzsanna Győri; Carmen Svastics; Sara Csillag (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Disability is a worldwide phenomenon: approximately 16% of the world's adult population aged 18 and older is disabled. WHO terms disability as an umbrella term, covering impairments, activity limitations and participation restrictions, including participation in the labour market. One possible solution to problems of low rates of labour market participation could be for people with disabilities to become entrepreneurs and run their own businesses. In our paper we would like to contribute to the growing body of empirical research on entrepreneurs with disabilities, highlighting the results of our exploratory qualitative research project, with a focus on ten Hungarian entrepreneurs with sight loss and physical disabilities. We explore and analyse the motivational background of people with disabilities establishing their own enterprises, showing forms of pull and push motivation
Keywords: 650; Entrepreneurial environment; Entrepreneurial motivation; Entrepreneurs with disabilities